Electrical discharge machining of silicon carbide using graphite electrode - Adnan, Muhammad Hafiz (2013)
Siliconized silicon carbide (SiSiC) is an advanced engineering ceramic, and it has excellent properties such as high hardness, high strength, high wear resistance and good chemical inertness at elevated temperature. Thus it has been used in cutting tools, seal rings, valve seats, bearing parts, and a variety of engine parts. The purpose of this study to determine suitable parameters setting on SiSiC by electrical discharge machining (EDM) using graphite electrode. In this work, a study on the influence of the most relevant EDM factors over surface roughness (Ra), material removal rate (MRR) and electrode wear ratio (TWR) has been carried out. Design of Experiment (DOE) with full factorial design experiments was employed as experimental design procedure to investigate the significant effects of each design factors. In order to test for curvature and measuring stability of process, four centre points will be added into the experiments. The mathematical model then was proposed based from the substantial result that would give impact to the SiSiC EDM performance. The design factors selected in this case were: peak current (IP), pulse on time (ONN), voltage (V) and pulse off time (OFF). Those parameters was widely used and interest by the machinists or researchers to control the EDM machine generator precisely to obtain desire machining output whether finishing, roughing or minimizing tool wear. Besides, prediction equation was proposed in order to obtain multiple desires machining output when machining SiSiC using graphite electrode.